1995
DOI: 10.1111/j.1476-5381.1995.tb15140.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of tumour necrosis factor‐α and endothelin‐1 to the increase of coronary resistance in hearts from rats treated with endotoxin

Abstract: 1 Inflammatory disease states predispose to myocardial infarction. Here we have investigated the effects of a systemic inflammatory response syndrome, i.e. lipopolysaccharide (LPS)-induced circulatory shock in rats, on coronary vascular tone. 2 Anaesthetized rats were given LPS (10 mg kg-', i.v.) and the hearts excised 180 min later for isolated perfusion at constant flow by the Langendorff technique. Once the ex vivo perfusion was started, the perfusion pressure strongly increased in these hearts compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 39 publications
2
28
1
2
Order By: Relevance
“…Therefore, more detailed studies are needed to better characterize whether IL-10 has antihypertensive properties in this experimental model. TNF-␣ was chronically infused to induce increased ET-1 expression, as previously described (2,10,18,29,47,51). We used prepro-ET-1 mRNA as a biomarker for ET-1 levels, since increased ET-1 plasma values may not reflect local production (12,30).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more detailed studies are needed to better characterize whether IL-10 has antihypertensive properties in this experimental model. TNF-␣ was chronically infused to induce increased ET-1 expression, as previously described (2,10,18,29,47,51). We used prepro-ET-1 mRNA as a biomarker for ET-1 levels, since increased ET-1 plasma values may not reflect local production (12,30).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that TNF-␣ induces a downregulation of eNOS, which results from a destabilization of eNOS mRNA with no effect on transcription (25,60). Morever, TNF-␣ release has been shown to increase plasma levels of ET-1 (6,18,58). Thus the observed reduction of renal eNOS expression and activity as well as ET-1 upregulation could be specific to high-intensity acute exercise.…”
Section: Exercise Training and Renal Vascular Reactivitymentioning
confidence: 99%
“…In another study (41) it was found that aerobic training, known to increase resting peripheral nervous system (PNS) activity (42,43), significantly reduced the production of tumor necrosis factor (TNF)-α by stimulated macrophages. TNF-α can provoke release of ET-1 from macrophages (11,12), and has been observed in combination with ET-1 to promote constriction in the coronary microvascular bed (44). During mental stress in patients with CAD, disinhibition of macrophages consequent to withdrawal of vagal efferent activity may thereby accelerate the production and release of ET-1 from macrophages and/or adjacent endothelial cells that secrete the peptide (17,45).…”
Section: A N G E R P a R A S Y M P A T H E T I C W I T H D R A W A mentioning
confidence: 99%